Metal hydroxide particles
Patent Information
- Application Number
- CN202610271182.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-07
- Filing Date
- 2026-03-06
- Publication Date
- 2026-10-16
AI Technical Summary
[0016] This invention provides metal hydroxide particles that can help produce batteries with good rate performance.
Smart Images

Figure CN122930894A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to metal hydroxide particles. Background Technology
[0002] In recent years, battery research and development has been actively underway. For example, in the automotive industry, research and development of lithium-ion batteries for battery electric vehicles (BEVs), plug-in hybrid electric vehicles (PHEVs), or hybrid electric vehicles (HEVs) is being advanced. Furthermore, various studies are being conducted on the positive electrode active materials and their precursors for batteries.
[0003] For example, Japanese Patent Application Publication No. 2014-506220 discloses a precursor material of an alloy oxide hydroxide represented by a specified chemical formula, and a lithium-ion battery cathode active material prepared using the precursor material.
[0004] Furthermore, Japanese Patent Application Publication No. 2024-086748 discloses particles containing a transition metal and additive elements unevenly distributed within the particles, comprising secondary particles formed by the aggregation of multiple primary particles. Each secondary particle has a central portion formed by the aggregation of multiple fine primary particles, located at the center containing the secondary particles. The secondary particles also have an outer peripheral portion formed by the aggregation of plate-like primary particles larger than the fine primary particles, located outside the central portion. Compared to the plate-like primary particles in the outer peripheral portion, the fine primary particles in the central portion contain the additive elements at a higher concentration. Additionally, Japanese Patent Application Publication No. 2024-086748 also discloses a positive electrode active material for lithium-ion secondary batteries using these transition metal composite hydroxide particles as a precursor. Summary of the Invention
[0005] From the perspective of improving battery performance, good rate performance is required. This invention was made in view of the above-mentioned realities, and its main objective is to provide metal hydroxide particles used as precursors for positive electrode active materials, which can help in the manufacture of batteries with good rate performance.
[0006] Method 1
[0007] A metal hydroxide particle, used as a precursor for a positive electrode active material, wherein the metal hydroxide particle is a secondary particle composed of aggregates of multiple primary particles, wherein the primary particles contain a transition metal element, and the particle size is defined as D when the total particle size of the primary particles, based on a volume basis and accumulating to 10% from the smallest particle side. 10 [μm], the particle size at 50% cumulative concentration is set as D. 50 [μm], the particle size at 90% cumulative concentration is set as D. 90When [μm], the primary particle satisfies 0.3 ≤ (D 90 -D 10 ) / D 50 .
[0008] Method 2
[0009] According to the metal hydroxide particles of method 1, wherein the primary particles satisfy (D 90 -D 10 ) / D 50 ≤5.0.
[0010] Method 3
[0011] According to method 1 or 2, the metal hydroxide particles, wherein the primary particles satisfy 0.5 ≤ D 50 ≤5.0.
[0012] Method 4
[0013] The metal hydroxide particles according to any one of methods 1 to 3, wherein the primary particles contain at least one of Ni, Co and Mn as the transition metal element.
[0014] Method 5
[0015] According to the metal hydroxide particles of method 4, wherein the primary particles contain Ni element as the transition metal element, and the proportion of Ni element relative to all transition metal elements is 50 mol% or more.
[0016] This invention provides metal hydroxide particles that can help produce batteries with good rate performance. Attached Figure Description
[0017] The features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will now be described with reference to the accompanying drawings, wherein the same reference numerals denote the same elements.
[0018] Figure 1 This is a schematic cross-sectional view illustrating the metal hydroxide particles of the present invention.
[0019] Figure 2 This is a schematic cross-sectional view illustrating the battery of the present invention. Detailed Implementation
[0020] The metal hydroxide particles of the present invention will now be described in detail. It should be noted that the figures described below are illustrative and may be exaggerated in size and shape for ease of understanding.
[0021] The metal hydroxide particles of the present invention are used as precursors for positive electrode active materials. Additionally, as... Figure 1 As shown, the metal hydroxide particles 10 are secondary particles formed by the aggregation of multiple primary particles 1. Furthermore, the primary particles 1 contain transition metal elements. The particle size of the primary particles 1, calculated based on volume and representing 10% from the smallest particle side, is defined as D. 10 [μm], the particle size at 50% cumulative concentration is set as D. 50 [μm], the particle size at 90% cumulative concentration is set as D. 90 [μm]. In this case, primary particle 1 satisfies 0.3 ≤ (D 90 -D 10 ) / D 50 .
[0022] According to the present invention, since the primary particle satisfies 0.3≤(D) 90 -D 10 ) / D 50 Therefore, it becomes a metal hydroxide particle that can help produce batteries with good rate performance.
[0023] It can be inferred that for positive electrode active materials, the more uniform the particle size of the primary particles, the more uniform the overall reaction of the positive electrode active material, and the better the battery characteristics such as rate performance. However, surprisingly, the inventors discovered that by varying the particle size of the primary particles in the positive electrode active material, the battery's rate performance actually improves. This is presumably because, with uniform primary particle size, the interior of the positive electrode active material, as secondary particles, becomes dense, making it difficult for the electrolyte to fully penetrate, and reducing the diffusion of Li ions. Therefore, the inventors discovered that by varying the particle size of the primary particles in the precursor particles of the positive electrode active material, the particle size of the primary particles in the positive electrode active material made using those precursor particles can also vary, thus completing this invention.
[0024] 1. Primary particle
[0025] The primary particles in this invention satisfy 0.3 ≤ (D 90 -D 10 ) / D 50 (D) 90 -D 10 ) / D 50 It means using D 50 The width of the overall distribution of particles as a baseline. (D) 90 -D 10 ) / D 50 A larger value indicates a wider distribution and a more dispersed particle size distribution. (D) 90 -D 10 ) / D 50It can be above 0.4. (D) 90 -D 10 ) / D 50 It can be above 0.5. (D) 90 -D 10 ) / D 50 It can be above 0.7. (D) 90 -D 10 ) / D 50 It can be above 0.9. (D) 90 -D 10 ) / D 50 It can be 1.0 or higher. (D) 90 -D 10 ) / D 50 It can be 1.5 or higher. (D) 90 -D 10 ) / D 50 It can be 2.0 or higher. (D) 90 -D 10 ) / D 50 It can be 2.3 or higher. (D) 90 -D 10 ) / D 50 It can be 2.5 or higher. On the other hand, (D) 90 -D 10 ) / D 50 For example, it can be below 5.0, below 4.8, below 4.0, or below 3.0.
[0026] Here, D 10 D 50 and D 90 These represent the particle size (μm) at 10%, 50%, and 90% cumulatively from the small particle side, respectively, based on a volumetric reference. 10 D 50 and D 90 For example, it can be measured by small-angle X-ray scattering (SAXS).
[0027] D 50 As long as the above formula (0.3≤(D) is satisfied) 90 -D 10 ) / D 50 There are no specific limitations. (D) 50 For example, it can be 0.5μm or larger, 1.0μm or larger, 1.2μm or larger, 1.5μm or larger, 2.4μm or larger, or 2.5μm or larger. On the other hand, D 50 For example, it can be below 5.0μm, below 4.5μm, below 4.0μm, below 3.5μm, or below 3.0μm.
[0028] D 10 As long as the above formula is satisfied and is less than the above D 50 There are no specific restrictions. D 10 For example, 0.1 μm or larger and 3 μm or smaller. Additionally, D 90 As long as the above formula is satisfied and is greater than the above D 50 There are no specific restrictions. D 90 For example, 5μm or larger and 10μm or smaller.
[0029] Regarding particle size (D) 10 D 50 and D 90 The particle size and deviation can be adjusted, for example, by changing the conditions in the crystallization process, as described in the examples described later. Specifically, by adjusting the supply rate and reaction temperature of the feed solution containing transition metal elements in the crystallization process, the growth of primary particles can be promoted or suppressed, thereby adjusting the particle size and its deviation. For example, increasing the supply rate and reaction temperature can be adjusted in the direction of promoting particle growth, while decreasing the supply rate and reaction temperature can be adjusted in the direction of suppressing particle growth. Furthermore, as described in the examples described later, the particle size deviation can be adjusted by alternating and repeating the dropping conditions that suppress particle growth with those that promote particle growth.
[0030] Primary particles are hydroxides containing transition metal elements. Examples of transition metal elements include Ni, Co, and Mn. Primary particles may contain at least one of Ni, Co, and Mn as a transition metal element, or they may contain two or more of these transition metal elements.
[0031] The primary particles preferably contain at least Ni as a transition metal element. The proportion of Ni relative to all transition metal elements is, for example, 30 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, or 80 mol% or more. On the other hand, the proportion of Ni is typically 100 mol% or less, 98 mol% or less, 95 mol% or less, 90 mol% or less, or 85 mol% or less.
[0032] Primary particles may contain Co as a transition metal element, or they may not contain Co. The proportion of Co relative to all transition metal elements may be, for example, 0 mol% or more, 3 mol% or more, 5 mol% or more, or 10 mol% or more. On the other hand, the proportion of Co may be, for example, 30 mol% or less.
[0033] Primary particles may or may not contain Mn as a transition metal element. The proportion of Mn relative to all transition metal elements may be, for example, 0 mol% or more, 3 mol% or more, 5 mol% or more, or 10 mol% or more. On the other hand, the proportion of Mn may be, for example, 30 mol% or less.
[0034] Primary particles can contain elements other than transition metals, oxygen (O), and hydrogen (H). Examples of these other elements include metals belonging to groups 12 through 14 of the periodic table. Examples of metals belonging to groups 12 through 14 include Zn, Al, Si, Ga, Ge, In, and Sn.
[0035] 2. Metal hydroxide particles
[0036] The metal hydroxide particles of the present invention are secondary particles formed by the aggregation of the aforementioned primary particles. The number of primary particles constituting the secondary particles is typically 2 or more, but can be 5 or more, or 10 or more. On the other hand, the number of primary particles constituting the secondary particles is not particularly limited, for example, it is 10,000 or less.
[0037] There are no particular limitations on the method for producing metal hydroxide particles; for example, the crystallization method described in the examples below can be cited.
[0038] The particle size of the secondary particles is, for example, 10 μm or more and 50 μm or less. Furthermore, the secondary particles preferably have internal voids (spaces where primary particles do not exist). The porosity of the secondary particles is, for example, 10% or more and 40% or less. The porosity of the secondary particles can be determined, for example, by image analysis of a cross-sectional SEM image using software.
[0039] 3. Positive electrode active material
[0040] The metal hydroxide particles of the present invention are used as precursors for positive electrode active materials. The present invention can also provide positive electrode active materials as calcined products of the aforementioned metal hydroxide particles. It can be deduced that the positive electrode active material of the present invention typically maintains the proportions of each transition metal element in the aforementioned metal hydroxide particles, as well as the structure such as particle size and particle size deviation. That is, the present invention can also provide positive electrode active materials as follows. It should be noted that the positive electrode active material of the present invention is typically a metal oxide particle.
[0041] The positive electrode active material used in the battery. This positive electrode active material is a secondary particle composed of aggregates of multiple primary particles. These primary particles contain Li, transition metal elements, and O. The particle size of the primary particles, representing 10% of the total particle size from the smallest particle side based on volume, is defined as D'. 10[μm], the particle size at 50% cumulative concentration is set as D' 50 [μm], the particle size at 90% cumulative concentration is set as D' 90 [μm]. In this case, the aforementioned primary particle satisfies 0.3 ≤ (D' 90 -D' 10 ) / D' 50 .
[0042] Regarding D' 10 D' 50 D' 90 And the above formula can be appropriately applied to D as described in "1. Primary Particles". 10 D 50 D 90 The content of the formula is also the same as that in "1. Primary Particles". The proportions of Ni, Co and Mn in the primary particles of the positive electrode active material are also the same as those recorded in "1. Primary Particles".
[0043] The composition of primary particles in the positive electrode active material is not particularly limited. For example, the composition of primary particles in the positive electrode active material can be represented by a material with the general formula Li. x Ni a Co b Mn c O y The composition represented by (0.1≤x≤1.5,0.5≤a≤1.0,0≤b≤0.3,0≤c≤0.3,a+b+c=1.0,1.5≤y≤2.1).
[0044] The method for manufacturing the positive electrode active material is not particularly limited. For example, it can be manufactured by adding a Li source (e.g., LiOH, Li2CO3) to the aforementioned metal hydroxide particles and then calcining, as described in the examples below. Furthermore, the positive electrode active material is used in batteries. Battery details will be provided later.
[0045] 4. Battery
[0046] The present invention can also provide a battery having a positive electrode active material layer containing the above-mentioned positive electrode active material. Figure 2 This is a schematic cross-sectional view illustrating the battery of the present invention. Figure 2 The battery 20 shown has a positive electrode active material layer 11, a negative electrode active material layer 12, and an electrolyte layer 13 disposed between the positive electrode active material layer 11 and the negative electrode active material layer 12. Figure 2 The battery 20 shown has a positive current collector 14 for collecting electrons in the positive electrode active material layer 11 and a negative current collector 15 for collecting electrons in the negative electrode active material layer 12. In the battery 10, the positive electrode active material layer 11 contains the aforementioned positive electrode active material.
[0047] (1) Positive electrode active material layer
[0048] The positive electrode active material layer contains the aforementioned positive electrode active material. Regarding the positive electrode active material, the content is the same as described in "3. Positive Electrode Active Material," therefore, the description is omitted here. The proportion of the positive electrode active material in the positive electrode active material layer is, for example, 20% by mass or more and 95% by mass or less.
[0049] The positive electrode active material layer may contain at least one of a conductive material, a binder, and an electrolyte, as needed. Examples of conductive materials include carbon-based conductive materials. Examples of carbon-based conductive materials include particulate materials such as acetylene black (AB) and Ketjen black (KB), fibrous materials such as vapor-grown carbon fiber (VGCF), carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of binders include rubber-based binders such as styrene-butadiene rubber (SBR) and butadiene rubber (BR), polycarboxylic acid-based binders such as carboxymethyl cellulose, and fluoride-based binders such as polyvinylidene fluoride (PVdF). Examples of electrolytes include the electrolytes described in "(3) Electrolyte Layer".
[0050] (2) Negative electrode active material layer
[0051] The negative electrode active material layer contains at least one negative electrode active material. Examples of negative electrode active materials include carbon-based active materials, Li-based active materials, Si-based active materials, and oxide-based active materials.
[0052] Examples of carbon-based active materials include graphite, soft carbon, and hard carbon. Graphite can be natural or artificial. Examples of Li-based active materials include Li and Li alloys. Examples of Li alloys include Li-Si alloys. Examples of Si-based active materials include Si and SiC composite active materials, Si alloys, and Si oxides. Examples of SiC composite active materials include active materials with Si or Si alloys supported on a carbon support. Examples of oxide-based active materials include Li₄Ti₅O. 12 Lithium titanate, etc.
[0053] The negative electrode active material layer may contain at least one of a conductive material, a binder, and an electrolyte. The conductive material, binder, and electrolyte are the same as those described in "(1) Positive electrode active material layer".
[0054] (3) Electrolyte layer
[0055] The electrolyte layer is a layer disposed between the positive electrode active material layer and the negative electrode active material layer, and it contains at least an electrolyte. The electrolyte is, for example, a liquid electrolyte (electrolyte).
[0056] Non-aqueous electrolytes can be listed as examples. Non-aqueous electrolytes include those containing lithium salts and non-aqueous solvents. Examples of lithium salts include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6; and organic lithium salts such as LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, and LiC(SO2CF3)3.
[0057] Examples of non-aqueous solvents include ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).
[0058] The electrolyte layer may have a membrane impregnated with the aforementioned electrolyte. Materials for the membrane may include those already known.
[0059] (4) Battery
[0060] The battery preferably has a positive current collector for collecting current in the positive electrode active material layer and a negative current collector for collecting current in the negative electrode active material layer. Examples of materials for the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. On the other hand, examples of materials for the negative electrode current collector include SUS, copper, nickel, and carbon. Furthermore, the battery of the present invention can have an outer casing that houses the power generation elements (positive electrode active material layer, electrolyte layer, and negative electrode active material layer). Examples of outer casings include a shell-type outer casing and a laminated outer casing.
[0061] The battery of the present invention is typically a lithium-ion battery. Furthermore, the battery of the present invention can be a primary battery or a secondary battery, but a secondary battery is preferred. This is because it can be repeatedly charged and discharged, making it useful, for example, as a vehicle battery. Examples of applications for lithium-ion batteries include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), battery electric vehicles (BEVs), gasoline vehicles, and diesel vehicles. It is particularly preferred for use as a power source for driving hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or battery electric vehicles (BEVs). Additionally, the battery can also be used as a power source for mobile bodies other than vehicles (e.g., railway vehicles, ships, aircraft), and as a power source for electronic products such as information processing devices.
[0062] It should be noted that the present invention is not limited to the embodiments described above. The embodiments described above are merely illustrative, and any embodiment having a substantially the same structure and performing the same effect as the technical concept described in the claims of the present invention is included within the technical scope of the present invention.
[0063] Comparative Example 1
[0064] Production of precursor particles
[0065] The precursor particles (metal hydroxide particles) of the positive electrode active material are prepared as follows.
[0066] Preparation of raw material aqueous solution
[0067] First, NiSO4, CoSO4, and MnSO4 are prepared as raw materials and dissolved in ion-exchange water to prepare a raw material aqueous solution. The molar ratio of Ni, Co, and Mn in the raw material aqueous solution is Ni:Co:Mn = 8:1:1. Furthermore, the concentration of the raw material aqueous solution (the proportion of all raw materials to the raw material aqueous solution) is 30% by mass.
[0068] Crystallization
[0069] A certain amount of NH3 aqueous solution was added to the reaction vessel, and the vessel was purged with nitrogen while stirring. NaOH aqueous solution was then added to the reaction vessel, maintaining an alkaline pH (pH=11) and a constant temperature, while the raw material aqueous solution and NH3 aqueous solution were added dropwise over 3 hours. The raw material aqueous solution was supplied at a rate of 5 mL / min, and the reaction temperature was 40 °C. Furthermore, the NH3 concentration was maintained at 15 g / L by adjusting the amount of NH3 aqueous solution added. This yielded a crystallized product (precipitate).
[0070] Washing and drying
[0071] The precipitate was recovered by filtration and washed with ion-exchanged water. Then, it was dried at 120°C for 16 hours to obtain precursor particles.
[0072] Production of positive electrode active material
[0073] The precursor particles and Li source (LiOH) were mixed using a mortar and pestle. The molar ratio of Li relative to the total transition metal elements contained in the precursor particles was 1.1. The resulting mixture was calcined in a muffle furnace at 900°C for 10 hours. The calcined body was then pulverized using a jet mill, and the particle size was adjusted to obtain the positive electrode active material.
[0074] Battery manufacturing
[0075] A battery was fabricated using the obtained positive electrode active material. Specifically, a thin-film coater (manufactured by AllGlide Co., Ltd.) with film thickness adjustment function was used to coat the positive electrode composite material paste onto the surface of a metal foil serving as the positive electrode current collector. The positive electrode composite material paste contained positive electrode active material, conductive material (acetylene black), and binder (polyvinylidene fluoride) in a mass ratio of positive electrode active material: conductive material: binder = 88:10:2. Then, it was dried at 80°C for 5 minutes using a dryer to obtain a positive electrode having a positive electrode current collector and a layer of positive electrode active material.
[0076] Next, using a thin-film coater with film thickness adjustment function (manufactured by AllGlide Co., Ltd.), the negative electrode composite paste was coated onto the surface of the metal foil serving as the negative electrode current collector. The negative electrode composite paste contained a negative electrode active material (natural graphite) and binders (SBR and CMC). Then, it was dried at 80°C for 5 minutes using a dryer to obtain a negative electrode with a negative electrode current collector and a layer of negative electrode active material. Next, a 1M LiPF6 solution was prepared as the electrolyte. The solvent for the electrolyte was a mixed solvent prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of EC:DMC:EMC = 3:4:3. Using the above positive electrode, negative electrode, and electrolyte, a wound cylindrical battery was obtained.
[0077] Example 1
[0078] Except for changing the dropping conditions in the above crystallization process, precursor particles were prepared in the same manner as in Comparative Example 1.
[0079] A first dropping treatment with a feed rate of 4 mL / min and a reaction temperature of 35°C for 10 minutes, followed by a second dropping treatment with a feed rate of 6 mL / min and a reaction temperature of 45°C for 10 minutes, constitutes one cycle. Repeat this cycle until the total dropping time reaches 3 hours.
[0080] In addition to using the obtained precursor particles, a positive electrode active material and a battery were obtained in the same manner as in Comparative Example 1.
[0081] Example 2
[0082] Except for changing the dropping conditions in the above crystallization process, precursor particles were prepared in the same manner as in Comparative Example 1.
[0083] A first dropping treatment with a feed rate of 3 mL / min and a reaction temperature of 30°C for 10 minutes, and a second dropping treatment with a feed rate of 7 mL / min and a reaction temperature of 50°C for 10 minutes, constitutes one cycle. Repeat the above cycle until the total dropping time reaches 3 hours.
[0084] In addition to using the obtained precursor particles, a positive electrode active material and a battery were obtained in the same manner as in Comparative Example 1.
[0085] Example 3
[0086] Except for changing the dropping conditions in the above crystallization process, precursor particles were prepared in the same manner as in Comparative Example 1.
[0087] A first dropping treatment with a feed rate of 2.5 mL / min and a reaction temperature of 30°C for 10 minutes, and a second dropping treatment with a feed rate of 7.5 mL / min and a reaction temperature of 55°C for 10 minutes, constitutes one cycle. Repeat the above cycle until the total dropping time reaches 3 hours.
[0088] In addition to using the obtained precursor particles, a positive electrode active material and a battery were obtained in the same manner as in Comparative Example 1.
[0089] Example 4
[0090] Except for changing the dropping conditions in the above crystallization process, the precursor particles were prepared in the same manner as in Comparative Example 1.
[0091] A first dropping treatment with a feed rate of 2 mL / min and a reaction temperature of 30°C for 10 minutes, followed by a second dropping treatment with a feed rate of 8 mL / min and a reaction temperature of 60°C for 10 minutes, constitutes one cycle. Repeat this cycle until the total dropping time reaches 3 hours.
[0092] In addition to using the obtained precursor particles, a positive electrode active material and a battery were obtained in the same manner as in Comparative Example 1.
[0093] evaluate
[0094] Particle size determination
[0095] For the metal hydroxide particles (precursor particles of the positive electrode active material) prepared in Comparative Example 1 and Examples 1-4, the particle size (D) was determined by small-angle X-ray scattering (SAXS). 10 D 50 and D 90 Furthermore, (D) is calculated from the obtained value. 90 -D 10 ) / D 50 The results are shown in Table 1. It should be noted that in the SAXS, the range of 0° ≤ 2θ ≤ 10° was measured using a SmartLab device manufactured by Rigaku Corporation, and the measurement was fitted using the analysis software included with the device. Then, D was calculated from the obtained distribution curve. 10 D 50 and D 90 .
[0096] Ratio test
[0097] The rate performance of the batteries fabricated in Comparative Example 1 and Examples 1-4 was evaluated. Specifically, the batteries were charged and discharged at current rates of 0.1C or 1C within a voltage range of 2.5-4.25V, and the discharge capacity at 0.1C and 1C was measured. The ratio (%) of the discharge capacity at 1C to the discharge capacity at 0.1C was then calculated, and the rate performance was compared. The results are shown in Table 1.
[0098] Table 1
[0099] As shown in Table 1, it was confirmed that by using the positive electrode active material made from the metal hydroxide particles of the present invention in the battery, the rate performance of the battery improved. It should be noted that since the positive electrode active material is made by sintering the metal hydroxide particles, the proportion of each transition metal element in the metal hydroxide particles and the particle size (D) of the primary particles can be inferred. 10 D 50 and D 90 It was maintained.
Claims
1. A metal hydroxide particle, which is used as a precursor of a positive electrode active material, wherein, The metal hydroxide particles are secondary particles formed by the aggregation of multiple primary particles. The primary particles contain transition metal elements. Let D be the particle size that, based on volume, accumulates to 10% from the smallest particle side in the primary particles. 10 The particle size at a cumulative 50% is set as D. 50 The particle size at a cumulative 90% is set as D. 90 At that time, the primary particle satisfies 0.3 ≤ (D 90 -D 10 ) / D 50 , where D 10 D 50 and D 90 The unit is μm.
2. The metal hydroxide particles according to claim 1, wherein, The primary particle satisfies (D) 90 -D 10 ) / D 50 ≤5.
0.
3. The metal hydroxide particles according to claim 1, wherein, The primary particle satisfies 0.5 ≤ D 50 ≤5.
0.
4. The metal hydroxide particles according to claim 1, wherein, The primary particle contains at least one of Ni, Co, and Mn as the transition metal element.
5. The metal hydroxide particles according to claim 4, wherein, The primary particle contains Ni as the transition metal element. The proportion of Ni relative to all transition metal elements is 50 mol% or more.
Citation Information
Patent Citations
Alloy hydroxide and method for producing the same
JP2014506220A
Particle of transition metal complex hydroxide, positive pole active material for lithium-ion secondary battery, and lithium-ion secondary battery
JP2024086748A